Innovative Technologies in Construction Project Management for Performance Improvement - Waheed, Muhammad (International Journal of Science, Engineering, and Information Technology, 2023)
Construction delays are becoming the most important issue facing all organizations in the construction industry. The majority of building projects in Pakistan are dealing with a similar issue. The goals of the organizations involved in construction firms, including the client, contractor, consultant, management, and others, are to finish the work within the allotted time frame, within the allocated funds, and with high-quality results. Construction projects are heavily influenced by delays; if individuals are unaware of the reasons behind the delays, they will not be successful. The purpose of this study is to identify the causes that cause delays so that the organizations can enhance the project's success. To determine the duration issues, the construction group members—owners, contractors, consultants, engineers, etc.—are surveyed using a questionnaire.